Efektivitas Pelatihan Mendeley secara Daring di Era Pandemi Covid-19 bagi Mahasiswa Universitas Muhammadiyah Yogyakarta - Aidilla Qurotianti (Pustabiblia: Journal of Library and Information Science, 2022)
At the end of 2019 the COVID-19 pandemic hit the world, including Indonesia. Therefore, universities must adapt to the form of online lectures, including Mendeley’s online training services at the UMY library. During the training, the librarian discussed various things about Mendeley through Zoom. The purpose of this research is to find out how effective Mendeley’s online training is for students. This study uses mixed research (mix methods) using the explanatory sequential design model. The results of the questionnaire showed that as many as 54.5% of students considered Mendeley’s online training to be ineffective due to unstable network factors. However, the results of questionnaires and interviews show an increase in the ability to use Mendeley after attending online training. Based on the results of the study, it can be concluded that online learning is an alternative choice during the current pandemic in order to reduce the spread of the COVID-19 virus in the lecture environment. This also applies to the information literacy service provided by the UMY Library, namely the online Mendeley training.